Ecosystem based fisheries management in the western pacific - Glazier, Edward W.; Wiley InterScience (Online service) (Hoboken, NJ : Wiley, 2011)
"As the ecosystem-based trend in fisheries management continues to be implemented worldwide, a thorough background of this new management approach and resulting implementation strategies is needed. Ecosystem Based Fisheries Management in the Western Pacific presents a full picture of the process changes used in switching from target species based management to EBFM, using a region that is at the forefront of this widely accepted movement. Ecosystem Based Fisheries Management in the Western Pacific is the outgrowth of a series of three workshops convened by the Western Pacific Regional Fishery Management council. The book follows the logical approach of each workshop, beginning with an assessment of the current state of fisheries management, transitioning through the data sources and modeling systems used to advance EBFM, and ending with practical methodologies for more thorough global implementation in the future. Contributed by experts from the Pacific regions as well as the UK and Non-pacific States, this book is one of the first available compendiums on this important movement and will be applicable to aquaculture scientists and researchers, fisheries managers, policy makers, and maritime social scientists worldwide"--
Front Matter -- Colour Plates -- Section 1: Ecosystem Science and Planning. Introduction to Ecosystem Science and Planning / Jared Makaiau, Paul Dalzell, Gerard Dinardo, Charly Alexander, Svein Fougner, Dirk Zeller -- Data Sources -- Ecosystem Models and Modeling -- Ecosystem Indicators -- Working Groups -- Synthesis -- Section 2: Ecosystem Social Science and Planning. Background on Ecosystem Social Science and Planning / Edward Glazier -- Introduction to Ecosystem Social Science and Planning -- Ecosystem Social Science Models -- Social Science Data Sources -- Social and Economic Indicators and Applications for EAFM in the Pacific -- Synthesis: Toward Incorporating Social Science in EAFM -- Summary Conclusions -- Section 3: The Ecosystem Policy Workshop. Introduction to Ecosystem Policy / Edward Glazier -- Ecosystem Policy -- Opening Presentations -- Policy for Indigenous Resource User Groups -- Options for Community and Agency Interaction -- Conclusions and Recommendations -- Appendix A: Speaker Biographies -- Appendix B: Select Demographic Tables -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Fishery management -- Oceania; Ecosystem management -- Oceania; Fishery management -- Pacific Ocean; Ecosystem management -- Pacific Ocean; Agriculture; TECHNOLOGY & ENGINEERING -- Fisheries & Aquaculture; Ecosystem management; Fishery management; Oceania; Pacific Ocean; Electronic books